Methodology for materiality: interaction design research through a material lens - Wiberg, Mikael (Personal and ubiquitous computing, 2014)
Increasingly, human–computer interaction (HCI) is acknowledging the material dimensions of our subject. In doing so, a wide repertoire of methods is currently being explored for conducting interaction design research through a material lens. These methods range from material studies and studies in material cultures to methods borrowed from craft, designerly approaches to interaction design, sketching in hardware approaches, and so on. While we acknowledge these important attempts to approach the material dimensions of interaction design, it should also be noted that there is a lack of more systematic studies of methods that are, can be, or have been applied within HCI and interaction design to specifically explore interaction design through a material lens. So, there is a need for a methodology that acts as a guideline to material-centered interaction design research. In this paper, we address this need. More specifically, this paper contributes to this current state by presenting a methodology for methodological explorations in material-centered interaction design research. The development of this proposed methodology takes a point of departure in the methods available and applied so far. With grounding in design theory, this paper organizes these methods into a four-dimensional structure to guide deliberate choices of methods in different phases of interaction design research projects—that is, it serves as a framework for research design. The organizing structure for the proposed methodology follows the simple dialectic tradition in design to work back and forth between details and wholeness, materials and textures . In this paper, we describe the four dimensions of our framework and how these can be useful to guide research design aimed at advancing our understanding of the material dimensions of HCI. We illustrate how the proposed structure can be practically useful—both in advancing our studies of interaction design through a material lens and show how it brings us back to the roots of our profession—that is, back to a focus on the materials, the fundamental components of any computational composition.